2022
DOI: 10.1108/ilt-05-2022-0153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dimple textures on the tribological performances of tapered roller bearings under starved lubrication

Abstract: Purpose The purpose of this paper is to study the influence of dimple textures on the friction and wear properties of tapered roller bearings (TRBs) with many pattern parameters, e.g. diameter, depth and area density under starved lubrication. Design/methodology/approach The pattern parameters include the dimple diameter (D; 60, 100 and 200 µm), dimple depth (H; 5, 10 and 20 µm) and area density (S; 6%, 12% and 24%). Dimples were fabricated on the outer ring (OR) of TRBs using a laser marking machine. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The mechanism of the single-pattern pitting texture is described in Wang and Zhang (2023). In the compound pattern pit texture, the dense distribution of small pits facilitates the diffusion of lubricating oil, thus providing lubricating oil for the contact area of the rolling bearing friction system.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the single-pattern pitting texture is described in Wang and Zhang (2023). In the compound pattern pit texture, the dense distribution of small pits facilitates the diffusion of lubricating oil, thus providing lubricating oil for the contact area of the rolling bearing friction system.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that the tribological performances of materials with surface texture were indeed enhanced compared with those without texture (Rapoport et al , 2008; Wang and Zhang, 2023). Zhan et al (2019) studied the effects of laser-textured surfaces on tribological performance of 40Cr steel.…”
Section: Introductionmentioning
confidence: 99%